PEMIKIRAN KEAGAMAAN TAREKAT NAQSYABANDIYAH DI DESA SUKADATANG KECAMATAN CURUP UTARA KABUPATEN REJANG LEBONG - Kadar Najmiddin (Manthiq : Jurnal Filsafat Agama dan Pemikiran Islam, 2016)
Abstract: Religious Thinking of Naqshbandi Order in the Village of Sukadatang Disctrict of North Curup Rejang Lebong;This research is motivated by the controversy over the existence of followers of Naqsyabandiyah Sufism in in the village ofSukadatang district Rejang Lebong. The problems of this research are: 1).What are the factors supporting the growing followers  ofNaqsyabandiyah order  in the village ofSukadatang Northern  Curup District of Rejang  Lebong?  2) How does  the  practice patterns of thought  and  religious  viewof  the  Naqsyabandiyah followers  in  the  village  ofSukadatang Northern  Curup  District of Rejang  Lebong?.  This research is a  field research. Data collection techniques used  were  interviews  with informants who  directly related to the issues. The results  showed that the factors supporting the growing follower of Naqsyabandiyah sufi orderin  the village of Sukadatang Northern  Curup District of Rejang Lebong are; Firstly, the internal  factors of the sufi order which include;  the  spiritual needs of the  congregation followers,  leadership figures, regeneration is good,  adequate building facilities, and the majority of the followers  are middle  income. Secondly,  is the external factors which include; the support of the Government, JATMI, the Indonesian Ulema Council, and the public. As for the practice of SufiNaqsyabandiyah worshipers in the  village of Sukadatang are:  repentance bath,  allegiance, mysticism, perform  dhikr latha’if, and tawajuh. While the religious thought  of this order is the moral approach, because the whole practice and dhikr undertaken aim to cleanse themselves of all sins and reprehensible nature. According to them, each participant shall make suluk allegiance to teachers or tutors. About genealogy, the teachings of this sufi order must have a pedigree that can be justified, and how to connect communication between pedigree it could have been through communication with a pedigree who has died, for example through dreams.